KULTUR SEL OTAK DAN MATA IKAN KERAPU (Chromileptes altivelis) UNTUK REPLIKASI VIRAL NERVOUS NECROSIS (VNN) - Sumaryam, Sumaryam; Kusyairi, Kusyairi; Oetami, Sri; Suprapto, Hari; de Vries, Garry Cores (BERITA BIOLOGI, 2011)
The experiment was deal with propagat cell line from encephalon and retina of grouper Chromileptes altivelis.The cell was isolate propagation of method described following by Chen et al.(1982) from carp and crussian carp fin. The cell line from enchepalon and retina of grouper grew very fast and heavy in medium L-1S.The cell line were then used for viral replication giving,isolated virus with high pathogenicity indicated by mortal effect in short time after administration. The preservation of cell line is in 10% glycerol under -80Â°C for one year. Thawing will be done every 3 months to ensure the viability of the cell.